Genetic parameters for worm resistance in Santa Inês sheep using the Bayesian animal model. - RODRIGUES, F. N. (2021)
The objective of this study was to estimate the genetic parameters for worm resistance (WR) and associated characteristics, using the linear-threshold animal model via Bayesian inference in single and multiple-trait analyses.